2010
DOI: 10.1111/j.1365-2699.2009.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Using carbon isotope analysis of the diet of two introduced Australian megaherbivores to understand Pleistocene megafaunal extinctions

Abstract: Aim Australia lost a diverse assemblage of large marsupial herbivores in the late Pleistocene, with suggestions that the extinctions were biased towards browsers. In modern times two bovines, the Asian water buffalo (Bubalus bubalis) and banteng (Bos javanicus), have established feral populations in the Northern Territory, Australia. Buffalo have aggressively expanded throughout the savanna landscape, yet banteng remain near their point of introduction on the Cobourg Peninsula. We hypothesized that this differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…This view is based on our observation that forest distribution and savanna tree cover are broadly similar between Africa and Australia (Figs 2 and 4). The large herbivore niche has been entirely empty in Australia for around 45 000 years (Bowman et al. 2010b), albeit now filled by exotic grazers such as horses, donkeys and swamp buffalo in the savannas.…”
Section: Disturbance‐based Controlsmentioning
confidence: 99%
“…This view is based on our observation that forest distribution and savanna tree cover are broadly similar between Africa and Australia (Figs 2 and 4). The large herbivore niche has been entirely empty in Australia for around 45 000 years (Bowman et al. 2010b), albeit now filled by exotic grazers such as horses, donkeys and swamp buffalo in the savannas.…”
Section: Disturbance‐based Controlsmentioning
confidence: 99%
“…1). Buffalo have a generalist diet, and their success in northern Australian signals they are well adapted to the region's harsh monsoonal environment (Bowman et al 2010b). We found that the current population of free-ranging swamp buffalo has high fertility rates (i.e.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, the smaller founder population (n = 20) of banteng (Bos javanicus) was introduced to Australia in the 1820s (Bradshaw et al 2007b); however, the species did not spread widely across northern Australia and, currently, between 5000 and 7000 animals (Bradshaw et al 2007b) remain close to the introduction site on the Cobourg Peninsula (Bowman et al 2010b). It has been proposed that the banteng's restricted habitat use and specialised browser diet is largely responsible for limiting the invasive capacity of the species (Bowman et al 2010b), and that this constrains population growth (Choquenot 1993) and dispersal capability (Bowman et al 2010b). There is little evidence of environmental impacts from banteng beyond browse lines on palatable trees, and trampling vegetation on trails and resting areas (Bowman and Panton 1994).…”
Section: History Of Buffalo and Banteng Introductionsmentioning
confidence: 99%
“…Introduced buffalo are a potentially valuable resource that could aid rural development in disadvantaged aboriginal communities of northern Australia. The buffalo population is increasing and they are well-adapted to the monsoonal tropics (Bowman et al 2010;. Indeed buffalo are an excellent low-maintenance resource because unlike cattle, they can maintain body condition and positive growth during times of low food or quality (Ford 1978(Ford , 1982Moran 1986Moran , 1992.…”
Section: Discussionmentioning
confidence: 99%
“…At higher densities, swamp buffalo cause major environmental damage such as saltwater intrusion into sensitive wetlands through the trampling of sensitive vegetation and browsing on remnant monsoon forest during the harsh late dry season when native pasture quantity and quality is declining (Bowman et al 2008;Braithwaite et al 1984;Petty et al 2007;Werner 2005;Werner et al 2006). Economically, buffalo are a major threat to Australia's livestock industry as hosts and vectors for diseases such as foot-and-mouth (Cousins and Roberts 2001;Ward et al 2007), and their broad dietary niche allows them to compete with cattle for pasture during the dry season (Bowman et al 2010). Socially, they pose a danger to human safety, especially for indigenous Australians in rural and remote areas (Albrecht et al 2009).…”
Section: Introductionmentioning
confidence: 99%